2021
DOI: 10.1155/2021/5556563
|View full text |Cite
|
Sign up to set email alerts
|

Extent, Distribution, and Causes of Soil Acidity under Subsistence Farming System and Lime Recommendation: The Case in Wolaita, Southern Ethiopia

Abstract: Soil acidity is one of the most important environmental threats to the Ethiopian highlands where the livelihood of the majority of people is reliant on agriculture. Yet, information regarding its extent, distribution, causes, and lime requirement at a scale relevant to subsistence farming systems is still lacking. This study (1) investigates the extent and spatial distribution of soil acidity, (2) identifies factors attributing to soil acidification, and (3) predicts the lime requirement for major crops. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The lowest pH values could be observed in soils of higher landscape regions, which could be due to the loss of exchangeable bases through erosion and runoff of the surface soil. Under these circumstances, the soil pH was lowered, and the activity of H + ions increased (Han et al, 2022;Laekemariam & Kibret, 2021). In general, our results showed that different land uses had different soil pH values, and this was consistent with the results of Akinde et al (2020) and Pourbabaei et al (2020).…”
Section: Land Use Land Cover and Phsupporting
confidence: 90%
See 1 more Smart Citation
“…The lowest pH values could be observed in soils of higher landscape regions, which could be due to the loss of exchangeable bases through erosion and runoff of the surface soil. Under these circumstances, the soil pH was lowered, and the activity of H + ions increased (Han et al, 2022;Laekemariam & Kibret, 2021). In general, our results showed that different land uses had different soil pH values, and this was consistent with the results of Akinde et al (2020) and Pourbabaei et al (2020).…”
Section: Land Use Land Cover and Phsupporting
confidence: 90%
“…The second explanation is agricultural intensification (Dar et al., 2021), which attempts to increase yield through the use of physiologically acidic fertilizers. Long‐term application of urea [(NH 2 ) 2 CO] (Ge et al., 2018) and diammonium phosphate [(NH 4 ) 2 HPO 4 ] in soil result in high H + concentrations, which lower pH (Laekemariam & Kibret, 2021; Salvator et al., 2019). The type of parent material is also important.…”
Section: Resultsmentioning
confidence: 99%
“…In actuality, tropical soils have lower fertility and nutritional defcits. Several factors are contributing to the deterioration of soil attributes [1][2][3][4], while depletion of soil nutrients and a lack of suitable management to restore the soils are major obstacles to food security [5,6]. Most soils in sub-Saharan African regions range in strength from strong to very strong acid soils; these soils often have unsuitable soil properties for crop production [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, acid soils reach 45.8 million hectares spread over various provinces and have unfavourable properties for several types of plants. The problems of cultivating plants in acid soils include low pH, high solubility of Al and Fe ions which bind phosphorus nutrients so that they are not available to plants [2]. Efforts to increase soil fertility and improve acid soil characteristics while maintaining environmental balance are using arbuscular mycorrhizal fungi.…”
Section: Introductionmentioning
confidence: 99%